2019
DOI: 10.1016/j.nedt.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in nursing students: An observational study

Abstract: Background: El burnout académico aparece por la aproximación de los estudiantes a las sobrecargas de las esferas laboral y académica, y puede repercutir negativamente en el aprendizaje y la calidad de los cuidados durante las prácticas clínicas. Objectives: Evaluar la presencia del síndrome de burnout en estudiantes de enfermería y detectar los principales factores estresores durante las prácticas clínicas. Design: Estudio observacional, descriptivo y transversal llevado a cabo entre enero y julio de 2017. Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 28 publications
1
27
1
3
Order By: Relevance
“…Concerning sex differences, the fact that women scored higher for procedural stress than men is consistent with the results reported by other studies (Suarez‐García, Maestro‐González, Zuazua‐Rico, Sánchez‐Zaballos, & Mosteiro‐Diaz, ; Valero‐Chillerón et al, ). However, in our study, the differences observed in emotional stress were less clear.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning sex differences, the fact that women scored higher for procedural stress than men is consistent with the results reported by other studies (Suarez‐García, Maestro‐González, Zuazua‐Rico, Sánchez‐Zaballos, & Mosteiro‐Diaz, ; Valero‐Chillerón et al, ). However, in our study, the differences observed in emotional stress were less clear.…”
Section: Discussionsupporting
confidence: 91%
“…It should also be noted that though the vast majority of literature related to burnouts in health care students is derived from studies in the field of medicine, similar stressful behaviors have also been reported in dental (Lambert et al, ; Pape et al, ), pharmacy (Nuffer et al, ; Lysak et al, ; Tetenbaum‐Novatt et al, ), and nursing students (Sun et al, ; Beanlands et al, ; Valero‐Chillerón et al, ). The common reasons for burnouts in these students also include an academic overload (Pape et al, ; Queen and Hess, ; Dames, ), unfamiliar working situations (Hennessy et al, ; Bing‐You et al, ; Budu et al, ), and fear of making mistakes with patients (Bronson, ; Worly et al, ; Riley et al, ).…”
Section: Challenges Of Present‐day Health Care Educationmentioning
confidence: 80%
“…These deficiencies in client communication skills of health care students are causing concern among educators (Silverman, et al, ; Augustyniak et al, ; Valero‐Chillerón et al, ) and policymakers (Strombach et al, ; Lysak et al, ). This situation has arisen primarily due to shortcomings in current training practices of these skills, which are mainly informal (Silverman, et al, ; Rosenman et al, ; Gonzalo et al, ; Abdel Meguid and Khalil, ; Raza et al, ), and most importantly lack structure (Baig and Mallu, ; Fond et al, ), dedicated teaching time (Stroud et al, ; Junod Perron et al, ), or distinct learning goals (Lamba et al, ; Jilla et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude is mental alertness that can be learned and organized from experience and has an impact on how to respond to other people, objects, and situations. The finding in the previous research stated that there is a significant negative relationship between the attitude of burnout syndrome among workers (Lestander, Lehto and Engström, 2016;Valero-Chillerón et al, 2019). This means that, if someone has a negative attitude toward career developments, then he/she will be in high probability to get a high level of burnout.…”
Section: Relationship Between Personal (Demographics) Factors and Burmentioning
confidence: 88%